Uji Perbandingan Aktivitas Ekstrak Kering Buah Asam Jawa (Tamarindus Indica L) dengan dan tanpa Kombinasi dengan Ekstrak Cair Daun Stevia (Stevia Rebaudiana B) terhadap Kadar Glukosa Darah Mencit Jantan (Mus Musculus) yang Diinduksi Aloksan - Mercya, Yovita; Mulyana, Deni (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Diabetes mellitus is a disorder that causes hyperglycemia due to insulin deficiency. Tamarind fruit is known to treat diabetes but the sour of tamarind fruit is often covered with sweeteners to improve the taste. This experimental study was conducted to compare the activity of  tamarind fruit with and without combination with stevia leaf liquid extract on blood glucose levels in male mice that had been induced by alloxan. After confirming that the mice's glucose levels were >200 mg/dl, 3 groups were tested, namely the test group 1 was given a solution of dry tamarind fruit extract, the test group 2 was given a combination of tamarind fruit extract solution and stevia leaf liquid extract, and the control group was given aqua distillate. The results of the paired t test against the test group 1 resulted in a decrease in blood glucose of 66.37% with p=0.00013 while the test group 2 was 35.35% with p=0.00035,  which means there is difference before and after treatment. Meanwhile, to see the difference in the decrease in blood glucose levels between groups, an independent t test was performed and obtained p=0.000002 which means that there is a significant difference in each test group.